Deciphering the impact of exogenous fatty acids on Listeria monocytogenes at low temperature by transcriptome analysis - Quilleré, Aurore; Darsonval, Maud; Papadochristopoulos, Angelos; Amoros, Alban; Nicolas, Pierre; Dubois-Brissonnet, Florence (Frontiers in Microbiology, 2024)
Listeria monocytogenes is a ubiquitous and psychrotrophic foodborne pathogen commonly found in raw materials, ready-to-eat products, and food environments. We previously demonstrated that L. monocytogenes can grow faster at low temperature when unsaturated fatty acids (UFA) are present in its environment. This could question the maintenance of food safety for refrigerated foods, especially those reformulated with a higher ratio of UFA versus saturated fatty acids (SFA) to fit with nutritional recommendations. In this study, we used transcriptomics to understand the impact of UFA on the behavior of L. monocytogenes at low temperature. We first demonstrated that fabK, a key gene in SFA synthesis, is up-regulated in the presence of UFA but not SFA at low temperature. L. monocytogenes can thus regulate the synthesis of SFA in its membrane according to the type of FA available in its environment. Interestingly, we also observed up-regulation of genes involved in chemotaxis and flagellar assembly (especially cheY and flaA) in the presence of UFA but not SFA at low temperature. TEM observations confirmed that L. monocytogenes acquired a remarkable phenotype with numerous and long-looped flagella only in the presence of UFA at 5°C but not at 37°C. As flagella are well known to be involved in biofilm formation, this new finding raises questions about the structure and persistence of biofilms settled in refrigerated environments using unsaturated lipid-rich products.